The distinctive histopathology of cicatricial alopecia caused by IgG4‐related disease. (15th February 2022) - Sperling, Leonard C.; von Kuster, Ken; Silver, Shane
Abstract: IgG4‐related disease (IgG4‐RD) is characterized by masses at multiple sites, a dense lymphoplasmacytic infiltrate containing numerous IgG4+ plasma cells, storiform fibrosis, and often elevated serum IgG4 concentrations. We present a third case of alopecia (in this instance, cicatricial) caused by IgG4‐RD. Based on our findings combined with those seen in two other cases, the histopathologic features of IgG4‐RD alopecia include: sparing of the epidermis, cicatricial (scarring) alopecia with a markedly decreased number of hairs, miniaturization of residual hairs, and total loss of the sebaceous glands. Groups of follicles with their associated sebaceous glands (follicular units) are replaced by an extremely dense infiltrate of lymphocytes and especially plasma cells. Histiocytic aggregates, both foamy and non‐foamy, may also be present. Variable degrees of fibroplasia may be present but are not an important feature in this type of alopecia.